Comparative Study of the National Defense Curriculum in Universitas Pertahanan and Universitas Pembangunan Nasional “Veteran” Jawa Timur - Sutrisno; Anajeng Esri Edhi Mahanani; Teddy Prima Anggriawan; Alvian Dwiangga Wijaya (Future Science, 2021)
The university's identity which in this case is intended as